Effectiveness and cost-effectiveness of a sustainable obesity prevention programme for preschool children delivered at scale ‘HENRY’ (Health, Exercise, Nutrition for the Really Young): protocol for the HENRY III cluster randomised controlled trial - Bryant, Maria; Burton, Wendy; Collinson, Michelle; Martin, Adam; Copsey, Bethan; Groves-Williams, Dawn; Foster, Alexis; Willis, Thomas A; Garnett, Philip; O'Cathain, Alicia (BMJ open, 2024)
IntroductionOne-fifth of children start school already overweight or living with obesity, with rates disproportionately impacting those living in the most deprived areas. Social, environmental and biological factors contribute to excess weight gain and programmes delivered in early years settings aim to support families to navigate these in order to prevent obesity. One of these programmes (Health, Exercise and Nutrition for the Really Young, HENRY) has been delivered in UK community venues (hereon named ‘centres’) in high deprivation areas since 2008 and aims to help families to provide a healthy start for their preschool children. We aim to establish the effectiveness and cost-effectiveness of HENRY, including its potential role from a wider systems perspective.Methods and analysisThis is a multicentre, open-labelled, two-group, prospective, cluster randomised controlled trial, with cost-effectiveness analysis, systems-based process evaluation and internal pilot. Primary analysis will compare body mass index (BMI) z-score at 12 months in children (n=984) whose parents have attended HENRY to those who have not attended. Secondary outcomes include parent and staff BMI and waist circumference, parenting efficacy, feeding, eating habits, quality of life, resource use and medium term (3 years) BMI z-scores (child and siblings). 82 centres in ~14 local authority areas will be randomised (1:1) to receive HENRY or continue with standard practice. Intention-to-treat analysis will compare outcomes using mixed effects linear regression. Economic evaluation will estimate a within-trial calculation of cost-per unit change in BMI z-score and longer-term trajectories to determine lifelong cost savings (long-term outcomes). A systems process evaluation will explore whether (and how) implementation of HENRY impacts (and is impacted by) the early years obesity system. An established parent advisory group will support delivery and dissemination.Ethics and disseminationEthical approval has been granted by the University of York, Health Sciences’ Research Governance Committee (HSRGC/2022/537/E). Dissemination includes policy reports, community resources, social media and academic outputs.Trial registration numberISRCTN16529380.